Methanol Toxic Optic Neuropathy (Characteristic and Evaluation of Therapy) - Ardiella Yunard; Syntia Nusanti; M. Sidik (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: Methanol toxic optic neuropathy is and optic neuropathy caused by methanolintoxication. Management of methanol toxic optic neuropathy is a therapeutic challenge and theoutcome is often unsatisfying. The aim of this study is to know the characteristics and evaluate theoutcome of corticosteroid therapy in methanol toxic optic neuropathy.Methods: Medical records of patients diagnosed with methanol toxic optic neuropathy from January2013 to December 2014 were reviewed retrospectively. Demographic characteristic, clinicalcharacteristic and visual acuity were evaluated.Results: During the period of January 2013 until December 2014, 31 patients were diagnosed withmethanol toxic optic neuropathy. All of them were males. The mean age was 31.87Â±9.23 years. Ocularsymptoms were found in 93.5%, most of them occured in 24-96 hours after methanol consumption.There were 85.4% patients at initial presentation had visual acuity (VA) less than 3 m finger counting,and 72.6% showed optic disc edema. Among the patients, 42% got intravenous high-dosemethylprednisolone, 19% got combination of intravenous high-dose methylprednisolone andhemodyalisis, 26% got oral methylprednisolone, and 3% got neuroprotector. VA improvement aftertherapy occured in 67.7%, no changes in 26.47%, and worsening in 5.88%. All patients who gottherapy in 6 days after methanol consumption showed VA improvement.Conclusion: The administration of intravenous high-dose steroids showed an improvement of visualstatus in most of the patients. Intravenous high-dose steroids gave benefit the visual status of patientswith methanol optic neuropathy, especially in patients with short interval between the consumption ofmethanol and starting the treatment.Â Keywords: methanol intoxication, optic neuropathy, methylprednisolone